Optimalisasi Kualitas Layanan pada Kantor Pengawasan dan Pelayanan Bea dan Cukai Sidoarjo Melalui Penerapan Digitalisasi Sistem CEISA - Danis Andrianto; Aris Sunarya; Ika Devy Pramudiana; M Khairul Anwar; Kresna Adhi Prahmana Putra (Sekolah Tinggi Ilmu Administrasi Yappi Makassar Jl. Sumba no 46, Kota Makassar, Sulawesi Selatan, 2025)
This study aims to analyze the impact of implementing the CEISA (Customs and Excise Information System and Automation) on service quality at the Customs and Excise Office in Sidoarjo using the service quality theory by Parasuraman, Zeithaml, and Berry. Employing a qualitative method, data were collected through interviews with users and system operators. The findings indicate that CEISA improves service efficiency, reliability, and security, with 85% of users stating that the infrastructure is adequate and 82.5% confident in data security. However, technical issues and resistance to change remain key challenges. Recommendations include improving infrastructure, providing continuous training, and enhancing data security to improve service quality and the institution's positive image.